2012
DOI: 10.1007/s00037-012-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Property Testing Lower Bounds via Communication Complexity

Abstract: We develop a new technique for proving lower bounds in property testing, by showing a strong connection between testing and communication complexity. We give a simple scheme for reducing communication problems to testing problems, thus allowing us to use known lower bounds in communication complexity to prove lower bounds in testing. This scheme is general and implies a number of new testing bounds, as well as simpler proofs of several known bounds.For the problem of testing whether a boolean function is k-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
145
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(146 citation statements)
references
References 52 publications
1
145
0
Order By: Relevance
“…Recently, a very elegant lower bound method for classical property testing was developed by Blais et al [38], based on communication complexity. In the basic setting of communication complexity [172,115], two parties (Alice with input x and Bob with input y) try to compute a function F(x, y) that depends on both of their inputs, using as little communication as possible.…”
Section: A Communication Complexity Method?mentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a very elegant lower bound method for classical property testing was developed by Blais et al [38], based on communication complexity. In the basic setting of communication complexity [172,115], two parties (Alice with input x and Bob with input y) try to compute a function F(x, y) that depends on both of their inputs, using as little communication as possible.…”
Section: A Communication Complexity Method?mentioning
confidence: 99%
“…Blais et al [38] showed for the first time how to derive property testing lower bounds from communication complexity. Their idea is to convert a T -query property tester for some property P into a protocol for some related communication problem F, by showing that 1-inputs (x, y) for F somehow correspond to elements of P, while 0-inputs (x, y) for F correspond to elements that are far from P. The more efficient the tester, the less communication the protocol needs.…”
Section: A Communication Complexity Method?mentioning
confidence: 99%
See 2 more Smart Citations
“…More recent motivations include connections to property testing [17]. A clever protocol of Håstad and Wigderson [63] gives an optimal O(m) communication protocol for m-disj, improving upon the trivial O(m log n) and the easy O(m log m) bounds.…”
Section: A Prescient Scheme For Sparse Disjointnessmentioning
confidence: 99%